Characterizing ontogenetic habitat shifts in marine fishes: advancing nascent methods for marine spatial management. Issue 6 (7th July 2017) - Galaiduk, Ronen; Radford, Ben T.; Saunders, Benjamin J.; Newman, Stephen J.; Harvey, Euan S.
Abstract: Niche requirements and habitat resource partitioning by conspecific fishes of different sizes are significant knowledge gaps in the species distribution modelling domain. Management actions and operations are typically concentrated on static habitats, or specific areas of interest, without considering movement patterns of species associated with ontogenetic shifts in habitat usage. Generalized additive models were used to model the body‐length–habitat relationships of six fish species. These models were used to identify subsets of environmental parameters that drive and explain the continuous length–habitat relationships for each of the study species, which vary in their degree of ecological and/or commercial importance. Continuous predictive maps of the length distributions for each of the six study species across approximately 200 km 2 of the study area were created from these models. The spatial patterns in habitat partitioning by individuals of different body lengths for all six study species provide strong evidence for ontogenetic shifts. This highlights the importance of considering ontogenetic processes for marine spatial management. Importantly, predictive hotspot maps were created that identify potential areas that accumulate individuals of similar life stages of multiple species (e.g., multispecies nursery areas). In circumstances where limited resources are available for monitoring and management of fish resources, predictive modelling is a valuable tool for studying previously overlooked processes such as ontogenetic habitat shifts. Predictive modelling provides crucial information that elucidates spatial patterns in community composition across mosaics of benthic habitats. This novel technique can contribute to the spatial management of coastal fish and fisheries by identifying areas that are important for different life history stages of multiple fish species.